Organizational and pedagogical conditions for artistic and aesthetic competence formation in children of senior preschool age - Demchuk, Kateryna; Myropolska, Natalia; Blyznyuk, Lyudmyla; Monke, Olena; Atorina, Victoria (My University, 2022)
Art as a way of reflecting the world in the process of artistic cognition enriches the child’s spiritual world, develops creative potential, expands the scope of his creative activity, and forms the basis of artistic and aesthetic competence, cultural creativity. The purpose of the academic paper lies in empirical verification of the results of forming organizational and pedagogical conditions in order to develop artistic and aesthetic competence among 5-6-year-old children. An experimental study of the organization of pedagogical conditions in the art workshop for the formation of artistic and aesthetic competence of 21 5-6-year-old children has been carried out. The major research methods are as follows: observation and content analysis of recordings made during the fine art activities of preschoolers. The pedagogical, practical and educational effectiveness of the following organizational and pedagogical conditions for the artistic activity of preschool children has been confirmed in the research, namely: the possibility of cooperation between children and a teacher, a professional artist; range of materials available; instructions and involvement of children in creative activities; discussions on works of art; conducting dialogue and attention to the children’s interests; raising children’s awareness through questions, suggestions, explanations and support in solving problems. The research has demonstrated that the creation of an artistic environment, the application of restrictions, taking into account the needs of children’s artistic activities, can create effective organizational and pedagogical conditions, deep and exciting art education. Preschool children, having a favourable stimulating environment, high-quality art materials, time and support on the part of preschool teachers, and a professional artist, are able to create works of art of a high aesthetic and artistic level developing their thinking, learning, theorizing knowledge and self-expression. The practical significance of the results obtained lies in using the child-centered approach and collaborative approach by teachers in order to stimulate children towards creating their own works of art.
Keywords: Artistic and aesthetic competence; organization of artistic activity; pedagogical conditions; preschool children; aesthetic competence